2011
DOI: 10.1158/0008-5472.can-11-1431
|View full text |Cite
|
Sign up to set email alerts
|

Dual Function of ERRα in Breast Cancer and Bone Metastasis Formation: Implication of VEGF and Osteoprotegerin

Abstract: Bone metastasis is a complication occurring in up to 70% of advanced breast cancer patients. The estrogen receptor-related receptor alpha (ERRa) has been implicated in breast cancer and bone development, prompting us to examine whether ERRa may function in promoting the osteolytic growth of breast cancer cells in bone. In a mouse xenograft model of metastatic human breast cancer, overexpression of wild-type ERRa reduced metastasis, whereas overexpression of a dominant negative mutant promoted metastasis. Osteo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
92
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(96 citation statements)
references
References 47 publications
2
92
1
1
Order By: Relevance
“…These include breast cancers, where a regulatory loop involving ERBB2 signaling has been documented (27,46,47). In addition ERRα promotes angiogenesis likely via the regulation of VEGF expression (28,30). Several reports have shown that ERRα is instrumental in controlling energy metabolism in tissues such as the liver, heart, or skeletal muscle through regulation of mitochondrial biogenesis, oxidative phosphorylation, glycolysis, pyruvate metabolism, and the TCA cycle (18,19,48).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include breast cancers, where a regulatory loop involving ERBB2 signaling has been documented (27,46,47). In addition ERRα promotes angiogenesis likely via the regulation of VEGF expression (28,30). Several reports have shown that ERRα is instrumental in controlling energy metabolism in tissues such as the liver, heart, or skeletal muscle through regulation of mitochondrial biogenesis, oxidative phosphorylation, glycolysis, pyruvate metabolism, and the TCA cycle (18,19,48).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover ablation of ERRα in knock-out mice delays ERBB2-induced mammary gland tumorigenesis (27). Furthermore overexpression of ERRα in xenografted breast cancer cells increases their metastatic capacities (28), in correlation with a massive induction Significance Several developmental and physiological processes require that cells display a controlled ability to migrate in an orientated manner. This capacity is also reacquired by certain cancer cells during their progression toward aggressiveness that allows them to establish distant metastases.…”
mentioning
confidence: 99%
“…Much attention has been paid to the role of ERRα in breast cancer due to its close relationship with ERs. Functional analyses performed on cancer cells suggest that ERRα can play regulatory roles in cancer growth through different mechanisms, including modulation of estrogen synthesis [66], cross-talks with pathways mediated by other hormone receptors (ERα, AR and GR) [52,64,67,68], enhancement of HIF-1 signaling [56], promotion of tumor aggressiveness by decreases the stability and activity of the RHOA protein [69] and tumor angiogenesis by targeting to VEGF gene [70][71][72] and induction of endothelial nitric oxide synthase (eNOS) expression [73], activation of oncogene ERBB2 or HER2 signaling [68] and mediation of oncogenic Ras-dependent anchorageindependent growth [74]. However, the functional role of ERRα in prostate cancer is still far from clear.…”
Section: Errsmentioning
confidence: 99%
“…Studies indicated that over expression of ERRa in xenografted breast cancer cells increases their metastatic capacities. 1,10,24 The expression of ERRa is highly detected in osteoblastic cells. 4 Further, it can confer methotrexate resistance via attenuation of reactive oxygen species (ROS) production in OS cells.…”
Section: Introductionmentioning
confidence: 99%